Eksistensi Kelembagaan Pertanian dalam Perspektif Petani dan Pengurus di Desa Talok Kecamatan Kalitidu - Dewi, Erika Triana; Nurhadi, Eko; Setiawan, Risqi Firdaus (Universitas Galuh, 2025)
The purpose of this study is to analyze the perceptions of farmers and management of the existence of agricultural institutions KUD, BUMDes, and Farmer Groups based by indicators of expectations, needs, and experiences. This research was located purposefully in Talok Village, Kalitidu Subdistrict, Bojonegoro Regency. The sampling method in this study used a non-probability sampling method with purposive sampling technique to sample 78 farmers and census sampling technique to sample 16 administrators. The analytical method used in this study uses the interval score calculation method to analyze the perceptions of farmers and management of the existence of agricultural institutions KUD, BUMDes, and Farmer Groups. The results of the research analysis showed that the perception seen from the indicators of expectations, needs, and experience of the existence of KUD, BUMDes, and Farmers Group.